Whistleblowers’ Role in Mitigating Fraud of Malaysian Higher Education Institutions - Mohamed, Intan Salwani; Belaja, Kristine; Rozzani, Nabilah (Asian Journal of Accounting Perspectives, 2019)
Research aim: The current study aims to discuss possible fraud occurrences that might happen in the setting of Malaysia higher education sector, as well as exploring the importance of whistleblowers as the primary source of information to investigators while looking into fraud cases involving universities. Design/ Methodology/ Approach: Literature review method is employed for this study. Research finding: With the rise of fraud cases in many sectors in Malaysia, many studies are concurrently emphasising on the crucial function of whistleblowing as an internal control mechanism of an organisation. However, the education industry is facing a challenging ethical dilemma with budget cuts experienced by higher education institutions, as they need to survive within the means of these allocations to ensure that they are operating smoothly, and to uphold their reputation. Theoretical contribution/ Originality: The discussion provided from this study on issues of fraud in Malaysian higher education institution and the vital role for individuals to blow the whistle as soon as they sense red flags is hoped to provide useful guides for organisations in designing distinct and unprejudiced whistleblowing hotlines to stop illegal organisational behaviour internally. Practitioner/ Policy implication: With fraud cases escalating, especially in universities, this study intends to create awareness among accounting professionals of the merits of whistleblowing to support reporting wrongdoings regarding their peers, possibly even before the effects are so disastrous that an organisation’s viability is in question. Research limitation/ Implication: As this is a conceptual paper, the findings are expected to lead towards further understanding of issues, and possible positive impacts on whistleblowing should be gathered and tested empirically. Keywords: Integrity, Whistleblowing, Higher Education Institutions Type of article: Conceptual paper JEL Classification: M00, M48